1986
DOI: 10.1007/bf00495785
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional observation of the nerve fibers along the cerebral blood vessels

Abstract: Three dimensional observation of the nerve fibers along the cerebral blood vessels was investigated by scanning electron microscopy. Electron probe X-ray microanalysis was also performed in the cerebral blood vessels treated with peroxidase-antiperoxidase immunohistochemistry intensified by nickel ammonium sulfate. Nerve fibers (2-8 microns in diameter) formed a plexus on the outer surface of the adventitia. After branching, the nerve fibers penetrated the blood vessel adventitia. Substance P-immunoreactive ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…A sparse nerve plexus associated with small terminal arterioles has also been shown in rat mammary glands (Fujiwara and Uehara, 1984). In an experiment on guinea pig cerebral arteries, only a part of a perivascular nerve plexus was revealed by SEM and an electron probe microanalysis method (Itakura et al, 1986). Our present SEM study on rat incisor teeth revealed for the first time the threedimensional architecture of perivascular nerve meshworks, which was very comparable to that revealed by immunohistochemistry for both CGRP and NPY immunoreactivity.…”
Section: Discussionsupporting
confidence: 80%
“…A sparse nerve plexus associated with small terminal arterioles has also been shown in rat mammary glands (Fujiwara and Uehara, 1984). In an experiment on guinea pig cerebral arteries, only a part of a perivascular nerve plexus was revealed by SEM and an electron probe microanalysis method (Itakura et al, 1986). Our present SEM study on rat incisor teeth revealed for the first time the threedimensional architecture of perivascular nerve meshworks, which was very comparable to that revealed by immunohistochemistry for both CGRP and NPY immunoreactivity.…”
Section: Discussionsupporting
confidence: 80%
“…Differences in the mechanism of action of VIP and substance P are also mirrored in the location of nerve endings for each peptide within the blood vessel wall. Itakura et al (1986) have shown that substance P-con taining fibers end in a meshwork pattern on the outer layers of the adventitia, whereas VIP fibers end in a spiral pattern on the inner layers. Differ ences between VIP and substance P in mechanism of action, anatomic location within the arterial wall, and nerve fiber type may indicate that substance P may not have a vasomotor function in the cerebral circulation, but that it may play a role in the media tion of nociception although the evidence of the axon reflex indicates that substance P may be in volved in both processes.…”
Section: Discussion Vasoactive Intestinal Peptide (Vip)mentioning
confidence: 99%